Sustainable consumption meets conspicuous leisure: a dual-theory exploration in luxury hospitality - Shrivastava, Priyanka; Hernandez, Sergio Romero; Hernandaz, Omar Romero (Frontiers in Sustainable Tourism, 2025)
As affluent travelers increasingly seek both exclusivity and environmental stewardship, luxury hospitality faces a core paradox: reconciling conspicuous consumption with authentic sustainability. This study investigates how Circular Business Practices (CBPs) shape guest motivations, satisfaction, and behavioral intentions in premium hospitality, drawing on Self-Determination Theory (SDT) and Veblen's Theory of the Leisure Class (TLC). A cross-sectional survey of 812 recent guests across luxury hotels in India, Dubai, Indonesia, and Mexico assessed perceptions of CBPs, intrinsic and extrinsic motivation, satisfaction, status signaling, and revisit intentions. Structural equation modeling reveals that CBPs significantly enhance both intrinsic (β = 0.073, p < 0.001) and extrinsic (β = 0.106, p < 0.001) motivations. Status signaling, as framed by TLC, strongly predicts behavioral intentions (β = 0.295, p < 0.001), while satisfaction contributes more modestly (β = 0.031, p < 0.05). Notably, an interaction effect (CBP × status) elevates satisfaction (β = 0.067, p < 0.001), suggesting that sustainability framed as exclusive enhances guest delight. The model demonstrates robust fit (CFI = 0.987; RMSEA = 0.071). While CBPs appear to boost loyalty, findings suggest that guest engagement with sustainability may reflect social signaling more than deep environmental commitment. This study extends SDT and TLC into the sustainable luxury domain, revealing a tension between ethical marketing and consumer desire for prestige. Managerially, it calls for visible, prestige-enhancing green practices, while urging more holistic sustainability frameworks that integrate social and ethical dimensions beyond performative environmentalism.